Myrmeleotettix Bolivar (Orthoptera, Gomphocerinae) in Anatolia on the basis of morphological and behavioural characters: data suggest a new species from southern end of the Anatolian refugium - Sirin, Deniz; Mol, Abbas; Ciplak, Battal (Zootaxa, 2011)
Myrmeleotettix Bolivar, 1914 (Orthoptera, Acrididae, Gomphocerinae) is a genus represented by nine species in the whole Palaearctic. It is poorly known in Anatolia except some records of M. maculatus. As for the other glacial refugia, cold preferring members of this genus are discontinuously distributed on high altitudes in Anatolia. Additionally, morphology is not sufficiently useful in taxonomy of gomphocerinae members for those producing a complicate courtship song. Thus an accurate taxonomy requires extensive materials and different character sources. In this study, the taxonomy of Anatolian Myrmeleotettix is reexamined on the basis of qualitative and morphometric morphology, and male calling and courtship songs. Song and morphology both suggest the existence of two species in Anatolia. The first is M. maculatus (Thunberg) which is distributed along the northern one-third of Anatolia in addition to other parts of West Palaearctic. The second is a new species, Myrmeleotettix ethicus sp. n. possibly endemic to the southwest corner of Anatolia. The new species can be easily distinguished from the most similar species M. maculatus by morphology as well as by song characters. The conclusions are: (i) similarities in courtship and calling songs of these two species may indicate that they are sister species (ii) from habitat preference and distribution patterns it can be inferred that they diverged following a cold period and the new species is a remnant of ancestral population in southern Taurus, and (iii) the new species is a range restricted, vulnerable species as is the case for many other taxa present in the Mediterranean Taurus biodiversity hotspot.